Tamimah dalam Perspektif Hadis - N, Nurmajedah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Tamimah is a rope that is worn by Arabs around the neck of children with the assumption that it can protect them from other diseases or eye diseases. Islam came and forbade all things related to shamanism in the form of amulets or spells and anything related to them is an evil that must be fought, except those that come from the Qur'an or spells that are ma'tsur. Based on this problem, the author wants to examine how the quality of the hadiths, both those that allow and forbid, and how to resolve them. Based on the results of the research, the authors found that the hadiths that seemed contradictory regarding the permissibility of using amulets could be compromised in order to avoid conflict and could be practiced together, considering that these hadiths met the criteria for the validity of the hadith. Thus, these traditions are maqbul hadiths with the status of valid traditions. So even though there are more hadiths that prohibit tamimah, all forms of amulets, whether from the Qur'an or not, are permissible under certain circumstances. The hadith about amulets is prohibited because some friends think that amulets are shirked because they deny belief in Allah swt. In fact, every form of the disease has a cure and the disease is cured with the permission of Allah swt.